Nyt redigeringssystem – overvejelser og valg - Rasmussen, Marie Bilde (Nordiske Studier i Leksikografi, 2006)
How to select a new dictionary writing system. Before introducing a new dictionary writing system it is important to describe the functionality of the writing system and what it requires and needs. These requirements and needs are normally described in a so-called list of requirements. The list of requirements is used to test the dictionary writing systems that are under considera-tion. In the Dictionary Department at Gyldendal Publishers we have prepared an extensive list of requirements listing more than 450 items. In this article I would like to pass on the experience from our tests. Firstly, I offer a discussion of the concept of a dictionary writing system. Then, I examine various dilemmas and conditions and in each case describe the prioritisation they may cause.